A contribution from the Chair and Vice-Chairs of the Advisory Scientific Committee to the discussion on the European Commission's banking union proposals - André Sapir; Martin Hellwig; Marco Pagano (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2012)
A European banking union is necessary to ensure the stability of the European financial system. This paper assesses the EU Commission's proposals for legislation to create a banking union in Europe. The EU Commission's proposal for a regulation creating a single supervisory mechanism is strongly supported. At the same time, a European resolution authority is essential for the credibility of the single supervisory mechanism.
Keywords: G28; 330; bank regulation; market integration